Analysis and functional prediction of reactive cysteine residues - Marino, Stefano M; Gladyshev, Vadim N (The Journal of biological chemistry, 2012)
Cys is much different from other common amino acids in proteins. Being one of the least abundant residues, Cys is often observed in functional sites in proteins. This residue is reactive, polarizable, and redox-active; has high affinity for metals; and is particularly responsive to the local environment. A better understanding of the basic properties of Cys is essential for interpretation of high-throughput data sets and for prediction and classification of functional Cys residues. We provide an overview of approaches used to study Cys residues, from methods for investigation of their basic properties, such as exposure and pK(a), to algorithms for functional prediction of different types of Cys in proteins.